2021
DOI: 10.1007/s40171-021-00267-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Flexible Strategies to Manage the COVID-19 Pandemic in the Education Sector

Abstract: COVID-19 has had a substantial impact on almost every field including the education sector. Due to the requirements for social distancing, the pandemic has provided an impetus for change in the education sector; technology-based sustainable education platforms not experienced previously have become essential. This research aims to propose flexible strategies to mitigate challenges of COVID-19 pandemic in the education sector of an emerging economy: Bangladesh. A total of 16 challenges and 19 flexible strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 84 publications
0
20
0
1
Order By: Relevance
“…This study confirmed how flexibility moves toward the SDGs. Previous studies highlight the positive relationship between sustainability and resilience within decisionmaking processes in risk measurement (Settembre-Blundo et al, 2021); of the potential benefits associated with the implementation of a flexible consumption tax (Gerbeti, 2021); of the decisive contribution of renewable energy globally (Ikram, 2021); and in the resilience of the education sector following pandermia (Ahmed et al, 2021).…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%
“…This study confirmed how flexibility moves toward the SDGs. Previous studies highlight the positive relationship between sustainability and resilience within decisionmaking processes in risk measurement (Settembre-Blundo et al, 2021); of the potential benefits associated with the implementation of a flexible consumption tax (Gerbeti, 2021); of the decisive contribution of renewable energy globally (Ikram, 2021); and in the resilience of the education sector following pandermia (Ahmed et al, 2021).…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%
“…Biswas ( 2020 ) evaluated the performance of Indian health care SC where pivot pairwise relative criteria importance assessment (PIPRECIA) method was used to find the criteria weights and then multi-attributive border approximation area comparison (MABAC), combined compromise solution (CoCoSo), and measurement of alternatives and ranking according to compromise solution (MARCOS), were used to find the rank of alternatives. Ahmed et al ( 2021 ) applied Pareto analysis and rough-decision making trial and evaluation laboratory (rough-DEMATEL) method to identify the challenges in the education sector of Bangladesh due to COVID-19 and proposed 19 flexible strategies to combat these challenges. Sarker et al ( 2021 ) developed a sustainability performance assessment model for the leather industry integrating several MCDM tools, i.e.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beyond the unprecedented nature of this health crisis, we observe that no sector of activity is exempt and that all organizations are affected. The repercussions are political, social, societal, economic and financial as well as organizational (Ahmed et al, 2021;Elias, 2021;Frimousse & Peretti, 2020;Paramita et al, 2021;Paul & Chowdhury, 2020;Ufua et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this current crisis that is unprecedented in scale and intensity since the Second World War, organizations cannot provide preconceived responses through the establishment of conventional emergency procedures to ensure their stability (Ahmed et al, 2021;Gajdzik & Wolniak, 2021).…”
Section: Introductionmentioning
confidence: 99%